Narrative review of the role of inflammation in gastroesophageal reflux disease. Can food allergies play a part? - Lucy Kensett Swain (Wiley, 2021)
Abstract Acid suppression is the accepted treatment for gastroesophageal reflux disease, despite being ineffective in one third of patients. Certain conditions presenting as reflux may later be attributed to food allergy (infant cow's milk allergy; eosinophilic esophagitis), but the role of food allergy in adult reflux disease has rarely been investigated. The mechanisms of gastroesophageal reflux disease are examined to explore potential subgroups within the population, such as undisclosed food allergy, which may determine the responsiveness to treatment. The relevant literature was searched systematically using ProQuest Dialog, yielding 113 papers that were evaluated for quality. The extracted evidence was formed into a mechanistic diagram representing the processes of disease. As yet, insufficient research exists to evaluate the relationship between food allergies and reflux in adults. Of significance, however, is the potential for multiple variables to affect the integrity of the esophageal mucosa, thereby allowing symptoms to emerge which are independent of acid exposure. Where nonacidic drivers of inflammation exist, acid suppression is unlikely to offer adequate symptom resolution and may serve to explain the high proportion of nonresponders in this group. The review concludes that symptoms of gastroesophageal reflux may emerge in response to the coexistence of physiological reflux and esophageal mucosal inflammation. The latter may arise due to reflux‐induced acid erosion, or due to alternative endogenous sources of inflammation. When a patient presents with refractory reflux and a history of allergic disease, the role of antigen‐induced inflammation should be considered for further investigation. Nonallergic individuals presenting with refractory reflux symptoms may benefit from further analysis of relevant co‐morbidities that have the capacity to compromise mucosal integrity, including obesity or psychological stress. The identification of specific mediators of inflammation in refractory reflux disease may enable the development of personalized treatment regimes which improve outcomes and reduce the reliance on acid suppressants.